Segmental body composition transitions in stroke patients: Trunks are different from extremities and strokes are as important as hemiparesis - Chang, Ke-Vin; Wu, Wei-Ting; Huang, Kuo-Chin; Han, Der-Sheng (Clinical nutrition (Edinburgh, Scotland), 2020)
Loss of muscle and bone mass is prevalent in the stroke population. Few studies have investigated the difference between having a stroke and hemiplegia and their influence on segmental body composition. This study aimed to evaluate the changes of body composition in the extremities and trunk of stroke patients in comparison with those of the healthy controls. Stroke patients with an onset of longer than 6 months and healthy participants matched by age and gender were recruited. Body weight, height, grip strength, and gait speed were measured, and a dual-energy x-ray absorptiometry was used to evaluate body composition. The generalized estimation equation model was employed to explore factors influencing extremity body composition, whereas those influencing the trunk body composition were analyzed using the general linear model. The study included 37 stroke patients and 37 healthy controls. The stroke group had significantly slower gait speeds, weaker hand grip strength, and a lower skeletal muscle index than the controls. Using 7.0 kg/m2 for men and 5.14 kg/m2 for women as the cutoff value for the skeletal muscle index, the prevalence of sarcopenia in our stroke group was found to be 48.6% (18/37). Being a stroke patient was associated with a decrease in bone (β = −21.89 g, p = 0.001) and lean mass (β = −210.46 g, p = 0.031) of the upper extremity and bone mass (β = −39.28 g, p = 0.008) of the lower extremity, regardless of the presence of limb paralysis. The limbs on the hemiplegic side had a further decline of extremity bone and lean mass. The stroke patients had an increase in trunk fat mass (β = 1392.68 g, p = 0.004) but not that of the extremities. Having a stroke and hemiparesis are both associated with body composition changes of the extremities, especially for bone and lean mass. A stroke is likely to increase the fat mass of the trunk rather than that of the extremities. A future cohort study is needed to clarify the causal relationship between stroke and transition of body composition and to investigate whether these changes are related to the disease prognosis or can be reversed by exercise and nutritional support.